Financial Ratio Analysis in Assessing Financial Performance at PT. Indofood Sukses Makmur, Tbk Listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 Period - Aprilia, Fista Lindu; Salsabila, Echa; Delani, Maisya; Pasi, Oktavia; Lubis, Nurmala Sari; Chrisna, Heriyati (Jurnal Riset Ilmu Pendidikan, 2024)
Evaluation of the financial performance of PT Indofood Sukses Makmur Tbk for the period 2020-2022 was carried out through a study with quantitative methods. The data source comes from annual reports available on the Indonesia Stock Exchange (IDX). Based on the calculation of profitability ratios (ROE, ROA, and NPM), it appears that the optimization of the use of equity, assets, and sales for profit is still not optimal. In terms of liquidity, although the current ratio and quick ratio are still below industry standards, the cash ratio indicates the effectiveness of cash management in maintaining short-term liquidity. Solvency analysis through DER and DAR reveals that the company still relies significantly on debt financing for operational activities, potentially increasing financial risk. It can be concluded that despite facing constraints in profitability and solvency, the company is able to maintain its short-term liquidity condition well.